Oral Biology Molecular Techniques and Applications - Seymour, Gregory J.; Cullinan, Mary P.; Heng, Nicholas C.K.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2010)
With so many major advances over the past two decades coming through the application of molecular biology and nanotechnology, it is essential that dental research, education, and practice keep pace with the rapid progress of science. In Oral Biology: Molecular Techniques and Applications, expert researchers in the field have provided a selection of in depth methods and techniques optimized for particular applications, which can be readily adapted to particular organisms or areas of interest. Divided into three convenient sections, the book covers the study of saliva, as it is a rich source of biomolecules for study at the molecular level, which may lead to the identification of susceptibility to particular diseases, the study of the microbial inhabitants that share the oral cavity with us, as well as a range of protocols that facilitate assessment of the molecular behavior of oral cells and tissues in health and during disease progression. Written in the highly successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and cutting-edge, Oral Biology: Molecular Techniques and Applications is an ideal resource not only to the new researcher but also to the seasoned laboratory veteran including cell biologists, microbiologists, and any researchers intent on delving into the vital world of oral biology.
Saliva Studies -- Gene Therapy of Salivary Diseases -- Collection, Storage, and Processing of Saliva Samples for Downstream Molecular Applications -- Proteomic Analysis of Saliva: 2D Gel Electrophoresis, LC-MS/MS, and Western Blotting -- Transcriptomic Analyses of Saliva -- Oral Microbiology -- The Oral Microbiota: General Overview, Taxonomy, and Nucleic Acid Techniques -- Microbial Community Profiling Using Terminal Restriction Fragment Length Polymorphism (T-RFLP) and Denaturing Gradient Gel Electrophoresis (DGGE) -- Protocols to Study the Physiology of Oral Biofilms -- Adhesion of Yeast and Bacteria to Oral Surfaces -- Quantitative Analysis of Periodontal Pathogens by ELISA and Real-Time Polymerase Chain Reaction -- Bacterial Viability Determination in a Dentinal Tubule Infection Model by Confocal Laser Scanning Microscopy -- Characterization of Anti-competitor Activities Produced by Oral Bacteria -- Natural Transformation of Oral Streptococci -- Use of In Vivo-Induced Antigen Technology (IVIAT) to Identify Virulence Factors of Porphyromonas gingivalis -- Oral Bacterial Genome Sequencing Using the High-Throughput Roche Genome Sequencer FLX System -- Use of a Yeast-Based Membrane Protein Expression Technology to Overexpress Drug Resistance Efflux Pumps -- Cells and Tissues -- Explant Culture of Embryonic Craniofacial Tissues: Analyzing Effects of Signaling Molecules on Gene Expression -- A Method to Isolate, Purify, and Characterize Human Periodontal Ligament Stem Cells -- Preclinical Methods for the Evaluation of Periodontal Regeneration In Vivo -- Proteomic Analysis of Dental Tissue Microsamples -- Immunological Techniques: ELISA, Flow Cytometry, and Immunohistochemistry -- Analysis of Immune Responses to Purified Recombinant Antigens of Periodontal Pathogens -- Single-Strand Conformation Polymorphism Analysis for the Diagnosis of T-Cell Clonality in Periodontal Disease -- Real-Time PCR Focused-Gene Array Profiling of Gingival and Periodontal Ligament Fibroblasts -- The Use of Gene Arrays in Deciphering the Pathobiology of Periodontal Diseases -- Bioinformatics Techniques in Microarray Research: Applied Microarray Data Analysis Using R and SAS Software.
Keywords: Microbiology; Pathology; Microbiology; Pathology